Corpus-based analysis of Tagalog/Pilipino/Filipino - written text - Ilao, Joel P.
This study seeks to determine if the development of the Philippine national language can be steered by identifying factors that correlate well with measurable facets of language development, such as the writing styles of Filipino writers and volume of publications written in the Tagalog/Pilipino/Filipino language. To achieve this goal, the largest collection of Tagalog/Pilipino/Filipino historical text containing 37.65 million words, published from the 1900s to the present and covering a wide range of domain and genre was built in order to conduct a longitudinal study of the writing styles of Filipino writers. The development of the national language was then charted based on a survey given to Filipino language advocates regarding their impressions on the effect of certain language-related Lexico-Stylometric (LS) features extracted from the collected text corpus and SPL trends were also made to see how such trends influence the level and nature of use of the national language. Computational models governing the observed trends in the Philippine national language were also applied, wherein language policy and planning activities that positively contributed to the progress of the Philippine national language were identified. Using the historical corpus covering a century-long analysis window, the development of Tagalog/Pilipino/Filipino?s system of orthography was tracked by observing how usage preferences changed over time. Philippine culturomic studies were also done using a historical news corpus covering a 2-year long analysis window. It was found in this study that there are observable trends in the writing styles of Filipino writers over the course of the 20th century, and that a majority of these Lexico-Stylometric trends do not statistically correlate with language-related socio-political and legislative (SPL) developments in the Philippine history. These observations are also apparent using Principal Components Analysis applied on the LS and SPL time-series data. The publication volume of Tagalog/Pilipino/Filipino documents, however, is positively influenced by language-related legislative and educational developments. The Publication of rulebooks (i.e. dictionaries, grammar and spelling books) by language institutes are shown to have a negative effect on the number of Tagalog/Pilipino/Filipino books published. Subjecting the Lexico-Stylometric and language-related Socio-political and Legislative development to computational modeling reveals that sociolinguistic conditions in the first hald of the 20th century are significantly different from that of the latter half of the 20th century, with favorable conditions starting from the 1960s onwards contributing to the quick rise of Filipiniana publication volume. Usage preferences for spelling variant groups within a century-long window period indicate that there are six categories of conventionalization rates in the Filipino language?s system of orthography. Philippine culturomic studies via normalized frequency graphs of selected search words and phrases show that there are four different news trends: (1) Filipino traditions with annually recurring plots, (2) disaster-related news with exponentially decreasing graphs, (3) fads with short-life spans, and (4) favorite Filipino conversation topics having consistent presence in news segments.